1996
DOI: 10.1002/adma.19960081219
|View full text |Cite
|
Sign up to set email alerts
|

Gold particle generation by spray pyrolysis

Abstract: 1020 0 VCH Verlagsgeselkhaft mbH, 0-69469 Weinheini, I996 0935-9648/96/

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…A number of examples of metals and their alloys (e.g., Ag, [145] Pd, [146] Au, [147] Cu, [148] Ni, [149] Co, [150] and Ag-Pd [151] ) production have been reported. Typical syntheses to produce metal or alloy particles involve a simple decomposition of aqueous metal salt (typically nitrate) solutions under an inert gas flow (e.g., N 2 or Ar).…”
Section: Preparation Of Fine Powders and Filmsmentioning
confidence: 98%
“…A number of examples of metals and their alloys (e.g., Ag, [145] Pd, [146] Au, [147] Cu, [148] Ni, [149] Co, [150] and Ag-Pd [151] ) production have been reported. Typical syntheses to produce metal or alloy particles involve a simple decomposition of aqueous metal salt (typically nitrate) solutions under an inert gas flow (e.g., N 2 or Ar).…”
Section: Preparation Of Fine Powders and Filmsmentioning
confidence: 98%
“…The XRD pattern of the precipitate showed that it was well-crystallized Ni(HCOO) 2 ⅐2H 2 O. ‡ Clearly, NO 3 Ϫ decomposed to gas species such as NO x , followed by the precipitation of Ni(HCOO) 2 from the solution. The similar vigorous processes can also occur within ‡ Powder Diffraction File, No.…”
Section: July 2001mentioning
confidence: 99%
“…Metals, metal oxides, and non-oxides can be readily produced by spray pyrolysis. [3][4][5] For electronic products such as multilayer ceramics and batteries, nickel is used for electrodes. 6 Because of its good performance and lower cost, compared with noble metals such as palladium and silver, nickel is replacing them and becoming one of the most important electrode materials.…”
Section: Introductionmentioning
confidence: 99%
“…45 46 USP has been applied for the preparation of micronsized fine powders of ceramic materials, metals and metal alloys (e.g., Ag, 47 Au, 48 Cu, 49 Ag-Pd 50 . Frequently, to synthesize a metal or alloy particles a simple decomposition method is used where an aqueous metal salt (e.g., nitrate) solutions (under an inert gas flow) are employed as metal precursors.…”
Section: Preparation Of Films and Fine Powdersmentioning
confidence: 99%